Shattered Schemata and Fragmented Identities: Men's Experiences of Antenatal Genetic Screening in Great Britain. (August 2013) - Dheensa, Sandi; Williams, Robert; Metcalfe, Alison
While pregnant women's views about antenatal screening have been widely researched, those of expectant fathers remain underexplored. Interviews were thus conducted with 12 men and 6 women, either during pregnancy or soon after birth. Findings suggested that the men started to construct a schema of their child and a paternal identity even before she/he was born. One of the paternal responsibilities men encountered was to participate in screening. However, men's ideas, beliefs, and feelings about being a father and about the future child were challenged by the receipt of screening results. Their child-schema became splintered into a wanted, imagined child and the at-risk fetus. Moreover, their paternal identity became fragmented into genetic and social components. Screening thereby caused some disruption in men's experience of impending fatherhood and of pregnancy, eliciting ambivalence and confusion. Further research is now required to explore the issues raised in the study.